Peningkatan Pelayanan Laboratorium Dengan Memprediksi Kedatangan Pasien Menggunakan Metode Monte Carlo - Eko Syaputra, Aldo; Eirlangga, Yofhanda Septi; Sapriadi, Sopi (JURNAL FASILKOM, 2023)
The number of patient visits to the laboratory is unstable sometimes decreasing and increasing, when the increase in the number of visits to the laboratory makes everything disrupted because the number of patients who come is not proportional to the staff who are working / assigned at that time in the laboratory. So that some patients do not even get thorough service and even some patients wait too long in the queue. This causes services in the laboratory to be hampered, disrupted and become less than optimal. So the laboratory must be able to overcome this problem by knowing the number of visits to the laboratory in the future. So the researchers conducted this study with the aim of providing accurate information regarding the prediction of the number of patient arrivals to the laboratory with the application of the Monte Carlo Method. This method is a method that is often used to solve problems that are often related to uncertainty. The data used in this study is the last 3 years of patient arrivals to the laboratory with the frequency of arrivals from January to December. The results of this research are compacted accuracy of 87% in 2020 and 91% in 2021. So that the laboratory can take action on services in the future and make this research as a reference material.